The Principle of Suitability Interpretation of Kant's Formula of the Law of Nature. Issue 161 (1st December 2019) - Furner, James
Abstract : In two recent articles I offered a solution to an old problem in Kant's account of the categorical imperative, that of finding a unitary interpretation of all four of the Groundwork's applications of the Formula of the Law of Nature (FLN). In this article I bring out the unity of this solution and defend the principle of suitability interpretation of FLN from objections raised by Samuel Kahn.